g*s-IRRESOLUTE MAPS IN TOPOLOGICAL SPACES - Tuyen, Ong Van (Hue University Journal of Science: Natural Science, 2018)
In 2009, A. I. El-Maghrabi and A. A. Nasef introduced a new class of sets between semi-closed and gs-closed sets called g*s-closed and gave some of their properties ([1]). In this paper, we introduce and study the concepts of three new class of maps, namely g*s-continuous maps, g*s-irresolute maps and g*s-closed maps. Moreover, we introduce the concepts of g*s-compactness of topological spaces.